Implementasi Model Pembelajaran Project Based Learning (PJBL) Terhadap Sikap Ilmiah Dan Kreativitas Siswa - Silvi Indriawati; Asep Ginanjar Arip; Sofyan Hasanudin Nur (Edubiologica Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2019)
The purpose of this study is 1) to describe the implementation of learning by implementing a project based learning model of learning towards scientific attitudes and student creativity on the concept of waste recycling, 2) to obtain data on the implementation of project based learning model learning can improve scientific attitudes on the concept of waste recycling, 3) to determine the implementation of project based learning model learning can increase student creativity on the concept of waste recycling, 4) to uncover student responses by implementing a project based learning model of learning towards scientific attitudes and student creativity on the concept of waste recycling.The method used in this research is the experimental method. With the technique of sampling by cluster random sampling in 2 classes each can get 34 students for the experimental class and 34 students for the control class. The research instrument used was the task and rubric of students' scientific attitudes, tasks and rubrics of creativity, questionnaires for student responses to learning and observation sheets of teacher and student activities. Data analysis techniques used were normality test, homogeneity test and hypothesis test. Based on the results of the analysis of the hypothesis test showed the value of t = 4.476 with Sig. 0.001 0.05 means that the implementation of the project based learning model of learning can improve scientific attitudes on the concept of waste recycling. Based on the results of hypothesis testing shows the value of t = 8.486 with Sig. 0.001 0.05 means that the implementation of the project based learning model of learning can increase student creativity in the concept of waste recycling. The conclusion in this study is the implementation of the project based learning model of learning can improve students' scientific attitudes and creativity on the concept of waste recycling in SMA Negeri 1 Cigugur.